LEGISLASI FIKIH EKONOMI PERBANKAN: SINKRONISASI PERAN DEWAN SYARIAH NASIONAL DAN KOMITE PERBANKAN SYARIAH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to further see the implementation of duties and functions of the National Sharia Board and Sharia Banking Committee and its relations to the legislation of economic bankingfiqh. In the development of Sharia Banking, synchronization between National Sharia Board and Sharia Banking Committee have been done by involving the National Sharia Board in the Committee Meeting to make Committee Recommendation to further be implemented as a Bank Indonesia Regulation. This researchfinds that the National Sharia Board has conducted its duties andfunctions in thefield of sharia economy in compliance with the DSN-MUI Decision 1/2000 on the Basic Guideline of National Sharia Board Indonesian Council of Ulema and DSN-MUI Decision 2/2000 Bylaws of the National Sharia Board Indonesian Council of Ulema. Keywords: sharia banking, Bank Indonesia regulation.